Albumin Levels and the Risk of Heart Failure in Patients Undergoing Coronary Angiography for Different Indications - Henning Johann Steffen; Michael Behnes; Lasse Kuhn; Philipp Steinke; Mahboubeh Jannesari; Fabian Siegel; Ibrahim Akin; Tobias Schupp (Journal of Clinical Medicine, 2026)
Background/Objective: Albumin has emerged as a prognostic marker across cardiovascular disease, but its independent association with heart failure (HF) in different clinical settings remains scarce. This study investigated the prognostic impact of baseline albumin levels in patients undergoing coronary angiography (CA) for different indications. Methods: Consecutive inpatients undergoing CA from 2016 to 2022 were retrospectively included at one institution and stratified into quartiles according to baseline albumin levels (Q1: 37 g/L). The primary endpoint was rehospitalization for HF at 36 months; secondary endpoints were coronary revascularization and acute myocardial infarction (AMI). Statistical analyses included Kaplan–Meier and Cox regression analyses. Results: A total of 7520 patients were included (median albumin: 34.3 g/L; IQR: 30.5–37.2 g/L). Lower albumin levels were associated with a higher comorbidity burden and more extensive coronary artery disease (three-vessel disease: Q1: 36.1% vs. Q4: 21.4%; p = 0.001). HF-related rehospitalization at 36 months increased progressively with lower albumin (Q1: 28.4% vs. Q2: 25.1% vs. Q3: 21.0% vs. Q4: 13.9%; p = 0.001). After multivariable adjustments, the lowest albumin group (